Journey to the Centre of the Ovale: A Novel, Combined Percutaneous Fluoroscopic and Image-Guided Approach to Biopsy a Meckel's Cave Lesion - Khan, Amad; Anwar, Durria; Hempenstall, Jonathan; Vajramani, Girish (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction The percutaneous Hartel's technique is a well-described approach to targeting lesions in the Meckel's cave. It is used as the standard approach for all percutaneous trigeminal neuralgia procedures for accessing the Gasserian ganglion through the foramen ovale, be it for a balloon compression, glycerol rhizolysis, or radiofrequency ablation. It has also been described in the literature as an approach to biopsy lesions in the Meckel's cave and cavernous sinus using fluoroscopic guidance; however, there were a significant number of nondiagnostic samples. No one to date has described a combined fluoroscopic and image-guided approach to improve safety and accuracy.Methods The patient had a 3-month history of left-sided facial numbness and a left VIth palsy causing diplopia and a squint. The computed tomography of the chest, abdomen, and pelvis was unremarkable as were the serum tumor markers. We describe the novel approach of using a percutaneous biopsy needle to obtain a cytological sample of a Meckel's cave lesion using a combination of X-ray and electromagnetic image guidance with use of StealthStation S8 System (Medtronic Sofamor Danek, Memphis, Tennessee, United States). The need for a craniotomy and its associated morbidity and technical challenges was therefore obviated.Results The procedure was performed under general anesthesia and eight core samples were sent to neuropathology for analysis. The lesion was histologically confirmed to be lymphoma, and the patient subsequently received oncological treatment. The patient had no immediate or postoperative complications, and the use of the aforementioned combined approach improved safety and accuracy of targeting the lesion in real time.Conclusion A combined percutaneous fluoroscopic and image-guided approach to biopsy a Meckel's cave lesion is recommended, as it improves safety and accuracy.
Keywords: foramen ovale; biopsy; skull base lesions; trigeminal neuralgia